Surface Engineering Of Titanium Based Metal For Cell Interaction - Hazan , Roshasnorlyza (2014)

(untitled)
This research focused on the titanium surface modification with nanotopography morphology of TiO2 nanotubes. Cell-metal interaction between TiO2 nanotubes and PA6 bone marrow stromal cells were studied to understand the TiO2 nanotubes parameters that affect the cell growth. To achieve objective of this research work, titanium foil was transformed into different dimensionalities of TiO2 nanotubes via simple anodization method and characterized. TiO2 nanotubes with inner diameter of 25 nm to 110 nm were successfully developed within 10 V to 40 V. Corrosion resistance was higher for sample anodizes at 10 V (25 nm-diameters). The length of the TiO2 nanotubes arrays were 2.2 μm after 3 hours anodization. Anatase, anataserutile and rutile phase was observed when TiO2 nanotubes subjected to anneal at 300 °C, 600 °C and 700 °C. Tubular structure destroy when anneal at 700 °C. Anatase phase give higher corrosion resistance because crystallized barrier oxide layer hinder the corrosion activity (corrosion rate = 0.31 nm/year). Cell morphology, adhesion,viability, immunocytochemistry, alkaline phosphatase activity, calcium deposition, Western Blot and immunophenotyping were done to evaluate PA6 cells interaction on TiO2 nanotubes accordingly. From this study, 45 nm-diameter, 2.2 μm-length nanotube and anatase-rutile mixture phase enhanced the PA6 cells growth. No materials elution after 3 days incubation with PA6 cells observed. The protein concentrations on TiO2 nanotubes were significantly higher than control due to large surface area and binding sites for cells to anchorage the substrate. Immunostaining expression for cytokeratin, Bromodeoxyuridine, CD34, IBMR3 and PI was positive on entire samples. From immunophenotyping analysis, PA6 cells were positive on CD49e, CD51 and CD73, suggested that PA6 cells on TiO2 nanotube arrays positively involved in extracellular matrix adhesion, bone marrow stromal cells interaction, immune system and mesenchymal stem cells differentiate. Importantly, fluorescence image shows PA6 cells cultured on TiO2 nanotubes did not have much alteration as compared to control with regard of no significant different from the fluorescence intensity. After 14 days, hydroxyapatite fully covered TiO2 nanotubes surface and enhance the PA6 cell growth and viability. These findings indicate that fine-tuning TiO2 nanotubes will be essential parameter in optimizing PA6 cell interaction.